The potential for using In Vitro techniques for germplasm collection - International Board for Plant Genetic Resources (1984)
This book is the outcome of a meeting of a subcommittee of IBPGR's Advisory Committee on In Vitro Conservation. It considers novel collecting techniques for vegetatively propagated species and material, such as coconut, which present practical problems.